Practical model-based testing a tools approach - Utting, Mark.; Legeard, Bruno (Amsterdam ; Boston : Morgan Kaufmann Publishers, 2007)
This book gives a practical introduction to model-based testing, showing how to write models for testing purposes and how to use model-based testing tools to generate test suites. It is aimed at testers and software developers who wish to use model-based testing, rather than at tool-developers or academics. The book focuses on the mainstream practice of functional black-box testing and covers different styles of models, especially transition-based models (UML state machines) and pre/post models (UML/OCL specifications and B notation). The steps of applying model-based testing are demonstrated on examples and case studies from a variety of software domains, including embedded software and information systems. From this book you will learn: * The basic principles and terminology of model-based testing * How model-based testing differs from other testing processes * How model-based testing fits into typical software lifecycles such as agile methods and the Unified Process * The benefits and limitations of model-based testing, its cost effectiveness and how it can reduce time-to-market * A step-by-step process for applying model-based testing * How to write good models for model-based testing * How to use a variety of test selection criteria to control the tests that are generated from your models * How model-based testing can connect to existing automated test execution platforms such as Mercury Test Director, Java JUnit, and proprietary test execution environments * Presents the basic principles and terminology of model-based testing * Shows how model-based testing fits into the software lifecycle, its cost-effectiveness, and how it can reduce time to market * Offers guidance on how to use different kinds of modeling techniques, useful test generation strategies, how to apply model-based testing techniques to real applications using case studies.
1 The Challenge; 2 The Pain and the Gain; 3 A Model of your System; 4 Selecting your Tests; 5 Testing from Finite State Machines; 6 Testing from Pre/Post Models; 7 Testing from UML Models; 8 Making Tests Executable; 9 The GSM 11.11 Case Study; 10 The ATM Case Study; 11 Putting it into Practice; Appendix; Index.
Includes bibliographical references (p. 409-418) and index.
Keywords: Computer software -- Testing; Computer software -- Testing -- Automation; Electronic books